Self-Control as a Mediator Between Social Environment, Adolescent Perceptions, and Ataraxia: A Study in Nahdlatul At-Thulab IPNU IPPNU - Saputra, Yahya Dwi Marta; Hakim, Ahmad Nu'man; Daryono, Rihab Wit (IAIN Palangka Raya, 2024)
Teenagers in this modern era often face various pressures and temptations that can influence their behavior and decisions. One aspect highlighted by research is self-control, which refers to an individual's ability to manage and control their behavior and internal impulses. The research aimed to explore the influence of Adolescent perceptions and Social Environment on teenagers' Ataraxia, as well as the mediating role of self-control in the context of prayer activities in the Nahdlatul At-Thulab IPNU IPPNU assembly. A quantitative survey method was used involving 60 teenagers in the Nahdlatul At-Thulab IPNU IPPNU prayer assembly, using probability sampling techniques with proportionate stratified sampling techniques. Data was collected through a questionnaire with a Likert scale. Data analysis was carried out using relevant statistical techniques. The research showed that there is a positive influence of Adolescent perceptions and Social Environment on the results of Teenager Ataraxia, with self-control mediating this relationship. The implications of this research are the importance of developing self-control skills and motivation in prayer meetings. Recommendations for further research are exploring other factors that influence adolescent perception, social environment, and self-control, as well as developing prayer activities to understand the dynamics of adolescent ataraxia.